Architects of terror paranoia, conspiracy and Anti-Semitism in Franco's Spain - Preston, Paul 1946- (William Collins, 2024)
From the preeminent historian of 20th century Spain Paul Preston, Architects of Terror is a new history of how paranoia, conspiracy and anti-Semitism was used to justify the military coup of 1936 and enabled the construction of a dictatorship built on violence and persecution. It is the previously untold story of how antisemitic beliefs were weaponised to justify and propagate the Franco overthrow of liberal Spain. The Spanish military coup of 1936 was launched to overturn the social and economic reforms of the democratic Second Republic, and its educational and cultural challenges to the established order. The consequent civil war was fought in the interests of the landowners, industrialists, bankers, clerics and army officers whose privileges were threatened.
Keywords: Geschichte 1936-1975; Verschwörungstheorie; Antisemitismus; Franquismus; Spanien; BIOGRAPHY & AUTOBIOGRAPHY / Historical; European history; Europäische Geschichte; Genocide & ethnic cleansing; Genozide und ethnische Säuberung; HISTORY / Europe / Spain & Portugal; HISTORY / Holocaust; HISTORY / Military / Other; National liberation & independence, post-colonialism; Nationale Befreiung und Unabhängigkeit, Postkolonialismus; POL064000; Postwar 20th century history, from c 1945 to c 2000; Revolutionen, Aufstände, Rebellionen; Revolutions, uprisings, rebellions; Spain